Answer: Choice B is correct
====================================================
Reason:
Focus on the numerator for now. The
is the same as
because we multiply the exponents. The general rule is
![(a^b)^c = a^(bc)](https://img.qammunity.org/2023/formulas/mathematics/high-school/100sbqz83g96w6ghj9srqqsbevfd6pl74e.png)
Alternatively we can think of it like this
![(11^8)^2 = (11^8)(11^8) = 11^(8+8) = 11^(16)](https://img.qammunity.org/2023/formulas/mathematics/college/2w8u5khfau07tiam19hnvtc8z20a6unspl.png)
So far we have
![((11^8)^2)/(11^3) = (11^(16))/(11^3)](https://img.qammunity.org/2023/formulas/mathematics/college/p4qzlwzh81rfo95cpbe81fo7e0ulh8iw8z.png)
------------
The last step is to subtract exponents due to the rule
and the order of subtraction is important.
Therefore,
![((11^8)^2)/(11^3) = (11^(16))/(11^3) = 11^(16-3) = 11^(13)](https://img.qammunity.org/2023/formulas/mathematics/college/8n21p94t0liuh0e4uuo1f8597pznejv784.png)